Large language models and AI-driven virtual laboratory for FrED and FrED factory: materials, products, and sustainable digital manufacturing - Ponce, Pedro; Anthony, Brian; Méndez, Juana Isabel; Bradley, Russel; Guerrero, Joan; Mata, Omar (Frontiers in Computer Science, 2026)
Developing new products requires innovative materials and advanced manufacturing methods. Consequently, establishing specialized laboratories capable of producing new products or enhancing manufacturing processes has become essential. Additionally, the complexity of product design, which involves multiple subsystems, requires extensive iteration, making the process both challenging and costly. Evaluating manufacturing conditions further adds to these difficulties and expenses. In response, cutting-edge laboratories utilizing advanced technologies have been developed. These laboratories offer several advantages, such as remote operation, where equipment can be controlled and tests conducted systematically from a distance. Moreover, Virtual Reality (VR) laboratories have gained traction due to their lower costs and flexibility. VR laboratories can be adjusted and used to train students and operators through immersive technologies that simulate real-world scenarios. This paper proposes an innovative virtual laboratory deployed on Oculus Quest 3 and Android devices. The VR laboratory interacts with users through large language models. The VR laboratory features a virtual Fiber Extrusion Device (FrED) developed at MIT, as well as expert avatars specializing in specific topics, offering solutions to develop soft skills. Furthermore, the VR experience is tailored to the user’s personality, enhancing the overall experience. Factory conditions are also simulated and optimized within the immersive laboratory using advanced optimization algorithms.